Industrial relations in Europe : traditions and transitions / edited by Joris Van Ruysseveldt & Jelle Visser. - Ruysseveldt, Joris Van; Visser, Jelle (Open University of the Netherlands ; SAGE, 1996)
This up-to-date introduction to the changing nature and context of industrial relations in contemporary Europe shows how different national systems of industrial relations offer varying models of relations between employers and workers.